Organizational Citizenship Behavior Islamic Perspective (OCBIP) pada Organisasi Tidak Berbasis Islam - Usman Usman (Jurnal Ilmiah Ekonomi Islam, 2021)
Organizational Citizenship Behavior (OCB) is a behavior performed by an individual or employee voluntarily helping each other without expecting an award or reward from the organization or company. This study aims to investigate the role of spirituality in the workplace and job characteristics on job satisfaction and Organizational Citizenship Behavior (OCBIP), especially in organizations that are not affiliated with Islam. The sample of this research is 122 respondents of BLU UPTD Trans Semarang employees and analyzed using Structural Equation Modeling (SEM). The results indicate that in an organizational environment that is not based on Islam,, spirituality in the workplace and job characteristics have a positive effect on job satisfaction and OCBIP.